Investigating the effects of workplace learning on employees’ performance in small medium enterprises in Singapore - Tan, Guo Qiang (American Journal of STEM Education, 2024)
Learning in the workplace has aroused scholarly interest over the past few decades. Many scholars have argued the positive significant effect that training has impacted job performance. The absence of existing research conducted in the Singapore context forms the bedrock for this study. The study adopted a quantitative method using a deductive approach and the research design is predictive and explanatory to establish the causal relationship between the variables. Employees (N=100) were randomly sampled. The model achieved constructs’ reliability and validity for both the inner model and the outer model. The results of this study established a significant relationship between workplace learning and employee performance (β=0.805, t=25.821, p=0.000).